Exploración neuropsicológica de la atención y la memoria en niños y adolescentes víctimas de la violencia en Colombia : estudio preliminar (2012)
ABSTRACT: This paper presents the preliminary results of a neuropsychological assessment of attention and memory carried out to a group of 35 children and adolescents that were victims of the armed conflict in Colombia; who presented symptoms of PTSD and / or depression. The data belong to a larger study that evaluates the neuropsychological effects of psychological trauma in a particular age group. The results suggest that participants experience lower attention and memory scores and it might increase during adolescence years. According to the characteristics of the sample, the authors consider that the neuropsychological symptoms, the inadequate behavior, and low cognitive performance might have a common component associated to situations of violence; which have not been further analyzed.